2020
DOI: 10.1177/0091217420982100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 lockdown on the incidence of deliberate self-harm injuries presenting to the emergency room

Abstract: Objective The World Health Organization declared COVID-19 a pandemic on 11th March 2020. The UK government introduced strict social distancing measures on 23rd March 2020, with the country put into a full lockdown to further halt the spread of the virus. The aims of this article are to ascertain whether there was a rise in the incidence of deliberate self-harm (DSH) presentations to the emergency department at a level one trauma center associated with the introduction of lockdown measures. Method An observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…A similar study conducted in Birmingham UK demonstrated an absolute increase in the presentations of deliberate self-harm to the emergency department. This study noted a rise in the percentage of these presentations from 1.98% to 3.69% (p < 0.001) when comparing 2019 to 2020 (21). These results may suggest a substantive negative impact of lockdown on mental health.…”
Section: Discussionmentioning
confidence: 56%
“…A similar study conducted in Birmingham UK demonstrated an absolute increase in the presentations of deliberate self-harm to the emergency department. This study noted a rise in the percentage of these presentations from 1.98% to 3.69% (p < 0.001) when comparing 2019 to 2020 (21). These results may suggest a substantive negative impact of lockdown on mental health.…”
Section: Discussionmentioning
confidence: 56%
“…Road traffic collision injuries still occurred with a similar proportionate incidence to the pre-lockdown period, as was also demonstrated in France [8] . The finding that deliberate self-harm injuries to the hand and upper limb did not increase, must be interpreted alongside recent data from the same hospital, that deliberate drug overdoses did increase during the same period [11] . This is suggestive of a broader increase in psychiatric morbidity that took place during lockdown, but that did not manifest as an increase in hand and upper limb injury.…”
Section: Discussionmentioning
confidence: 72%
“…In one university hospital in Ireland, emergency presentations for self-harm decreased in March-April 2020 before increasing in April-May 2020 [19] . In a trauma center in the UK, an increase in self-harm emergency presentations was observed [20] . Of note, an increase in more violent suicidal acts (penetrative lesions) has also been observed in a local hospital, UK [21] , which provides motivation to analyze the change in occurrence of self-harm as a function of the suicidal means and lethality of the act.…”
Section: Introductionmentioning
confidence: 99%